(Epi)genotype–phenotype correlations in Beckwith–Wiedemann syndrome: a paradigm for genomic medicine. Issue 4 (30th July 2015) - Mussa, A.; Russo, S.; Larizza, L.; Riccio, A.; Ferrero, G.B.
Abstract : Beckwith–Wiedemann syndrome (BWS) is the commonest overgrowth cancer predisposition disorder and represents a model for human imprinting dysregulation and tumorigenesis. BWS features can variably combine and present a widely variable range of severity in the phenotypic expression. This wide spectrum is paralleled at molecular level by complex (epi)genetic defects on chromosome 11p15.5 leading to disrupted expression of imprinted genes controlling growth and cellular proliferation. In this review, we outline the spectrum of clinical manifestations of BWS analyzing their (epi)genotype–phenotype correlations. The differences observed in the phenotypic profiles of BWS molecular subtypes allow a composite view of this syndrome with implications on clinical care, diagnosis, follow‐up, and management, and provide directions for future disease monitoring. Abstract :